Balto : 3-movie adventure pack [videorecording (DVD)]. - Brourman, Michele; McBroom, Amanda (Universal Studios Home Entertainment, 2016)
Balto: Balto, a sled dog in Alaska, makes an arduous journey to bring life-saving medicine to a town during a diphtheria epidemic.